Elevated maternal anxiety in the NICU predicts worse fine motor outcome in VLBW infants. (January 2018) - Greene, Michelle M.; Rossman, Beverly; Meier, Paula; Patra, Kousiki
Abstract: Aim: The literature is sparse with respect to the impact of elevated maternal psychological distress in the neonatal intensive care unit (NICU) on later neurodevelopmental outcome in VLBW infants. The objective of this study is to examine the impact of elevated maternal distress, defined as elevated depression, anxiety and perinatal-specific post-traumatic stress, during the NICU hospitalization on VLBW infant ND outcome at 20 months corrected age (CA). Methods: This was a prospective study of 69 mothers and their VLBW infants recruited in 2011–2012. Elevated maternal distress was collected by maternal questionnaire in the NICU. Elevated depression was quantified with the Center for Epidemiological Studies-Depression Scale, anxiety with the Spielberger State-Trait Anxiety Inventory and perinatal-specific post-traumatic stress with the Modified Perinatal Posttraumatic Stress Disorder Questionnaire. VLBW infant ND outcome was assessed using the Bayley Scales of Infant & Toddler Development-III at 20 months CA. Regression analyses determined the impact of elevated distress on ND outcome after adjusting for infant medical and maternal sociodemographic variables. Results: After controlling for infant and maternal covariates, elevated maternal anxiety in the NICU predicted lower fine motor scores at 20 months CA. Conclusion: Elevated maternal anxiety in the NICU is associated with adverse ND outcome in VLBW infants in the 2nd year of life. NICU-based support services may help mothers' quality of life and VLBW infant outcome. Highlights: Elevated maternal anxiety during VLBW infant NICU hospitalization predicted worse child fine motor outcome at 20 months CA Elevated maternal depression and perinatal specific post-traumatic stress in the NICU did not predict child ND outcome. Maternal anxiety in the NICU merits research to improve mothers' experience and to understand a modifiable ND risk factor.